Patient Preferences to Assess Value IN Gene Therapies: Protocol Development for the PAVING Study in Hemophilia - van Overbeeke, Eline; Hauber, Brett; Michelsen, Sissel; Goldman, Michel; Simoens, Steven; Huys, Isabelle (Frontiers in Medicine, 2021)
Introduction: Gene therapies are innovative therapies that are increasingly being developed. However, health technology assessment (HTA) and payer decision making on these therapies is impeded by uncertainties, especially regarding long-term outcomes. Through measuring patient preferences regarding gene therapies, the importance of unique elements that go beyond health gain can be quantified and inform value assessments. We designed a study, namely the Patient preferences to Assess Value IN Gene therapies (PAVING) study, that can inform HTA and payers by investigating trade-offs that adult Belgian hemophilia A and B patients are willing to make when asked to choose between a standard of care and gene therapy. Methods and analysis: An eight-step approach was taken to establish the protocol for this study: 1) stated preference method selection, 2) initial attributes identification, 3) stakeholder (HTA and payer) needs identification, 4) patient relevant attributes and information needs identification, 5) level identification and choice task construction, 6) educational tool design, 7) survey integration, and 8) piloting and pretesting. In the end, a threshold technique survey was designed using the attributes ‘Annual bleeding rate’, ‘Chance to stop prophylaxis’, ‘Time that side effects have been studied’ and ‘Quality of Life’. Ethics and dissemination: The Medical Ethics Committee of UZ KU Leuven/Research approved the study. Results from the study will be presented to stakeholders and patients at conferences and in peer-reviewed journals. We hope that results from the PAVING study can inform decision makers on the acceptability of uncertainties and the value of gene therapies to patients.